Phyto-synthesis of selenium nanoparticles using Mentha spicata (mint) extract and its larvicidal and antibacterial activities - Dayana Senthamarai, M.; Edwin Hillary, V.; Rajan, M.R.; Antony Ceasar, S.; Ignacimuthu, S. (Journal of Asia-Pacific entomology, 2025)
[Display omitted] •Vector-borne diseases spread by Aedes aegypti have ruined the lives of millions of people worldwide.•Synthesized selenium nanoparticles utilizing Mentha spicata leaf extract.•Antibacterial activity of Ms-SeNPs was tested against two gram-positive and negative food-borne pathogens.•The larvicidal effect of Ms-SeNPs on Ae. aegypti 3rd instar larvae is shown.•The impact of Ms-SeNPs on the expression of GST-2 and NO5-CYP450 genes in Ae. aegypti is tested. Major diseases like Zika, dengue, and chikungunya spread by Aedes aegypti have affected the lives of millions of people worldwide and continue to threaten billions. Controlling Ae. aegypti poses a significant challenge as the species has also evolved resistance to synthetic insecticides. The objective of the present study was to synthesize selenium nanoparticles (Se NPs) utilizing Mentha spicata (mint) leaf extract and evaluate their efficacy in managing Ae. aegypti third instar larvae and two gram-positive (Enterococcus faecalis and Staphylococcus aureus) and two gram-negative food-borne pathogens (Pseudomonas aeruginosa and Klebsiella pneumonia). The formation of Ms-SeNPs was confirmed using UV–Vis spectra (absorption peak at 268 nm), FTIR (functional peaks at 3418, 3006, 2915, 1632, 1382, 1200, 1047, 823, and 689 cm−1), and FESEM (rod shape). The size of the Ms-SeNPs was also analyzed using DLS (the average particle diameter is 111.1 nm). The Ms-SeNPs were also active on four food-borne pathogens and displayed strong inhibitory zones. The Ae. aegypti 3rd instar larvae that were treated with Ms-SeNPs showed promising larvicidal activities (LC50 value of 85.54 µg/ml and an LC90 value of 190.53 µg/ml). Furthermore, we examined the impact of Ms-SeNPs on the expression of functional genes, glutathione S transferase-2 (GST-2) and NO5-cytochrome P450 (NO5-CYP450), in Ae. aegypti. The overall findings validate the efficacy of Ms-SeNPs in managing both mosquitoes and bacterial pathogens, hence aiding in the development of versatile, environmentally friendly compounds.